2017
DOI: 10.1016/j.progpolymsci.2016.09.004
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamically tunable cell culture platforms for tissue engineering and mechanobiology

Abstract: Human tissues are sophisticated ensembles of many distinct cell types embedded in the complex, but well-defined, structures of the extracellular matrix (ECM). Dynamic biochemical, physicochemical, and mechano-structural changes in the ECM define and regulate tissue-specific cell behaviors. To recapitulate this complex environment in vitro, dynamic polymer-based biomaterials have emerged as powerful tools to probe and direct active changes in cell function. The rapid evolution of polymerization chemistries, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(75 citation statements)
references
References 243 publications
2
73
0
Order By: Relevance
“…This type of research has shown the possibility for different approaches to activate cellular pathways by enabling proper cell organization and exposure to bioactive surface molecules that can enhance differentiation. By tuning nanotopographical cues, cell behavior can be studied in a dynamic medium that further represents the matrix in which these cells could be applied [82, 83, 84]. …”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…This type of research has shown the possibility for different approaches to activate cellular pathways by enabling proper cell organization and exposure to bioactive surface molecules that can enhance differentiation. By tuning nanotopographical cues, cell behavior can be studied in a dynamic medium that further represents the matrix in which these cells could be applied [82, 83, 84]. …”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…Anunderstanding of the interaction of individual cells and cell clusters with their surrounding and in particular with biomaterials is regarded as key for the development of advanced therapies and approaches not limited to regenerative medicine. [1] In this context, it has been established that cell behavior may differ,f or example,i nt erms of cell adhesion, differentiation, and apoptosis,o nf lat 2D surfaces versus in 3D microwells. [2] Fors creening purposes,a dvanced 3D microarray fabrication techniques have been exploited, for instance in well-based formats for the study of cell-surface topography interactions.These studies revealed the impact of micro-and nanotopographies on metabolic activity,disclosed the mechanisms of biomaterials-induced mechano-transduction, [3] or helped to assess and rationalize the impact of topography on stem cell differentiation.…”
mentioning
confidence: 99%
“…Hence, maintenance of membrane proteins and ECM integrity is the most obvious advantages of thermoresponsive tissue culture dishes. This generally occurs because of disruption of adhesive junctions between basal side of cultured cells and grafted PNIPAAm layer by temperate trigger …”
Section: Discussionmentioning
confidence: 99%